Suspected caprine arthritis-encephalitis (CAE) in a Boer cross kid: a case report - Ho, Chai Ling; Abdullah, Faez Firdaus Jesse; Adamu, Lawan; Osman, Abdinasir Yusuf; Awang, Dayang Norhaizam; Taslim, Noorashimah; Taqiyuddin,; Saad, Mohd Zamri; Haron, Abdul Wahid; Saharee, Abdul Aziz (International Organization of Scientific Research, 2013)
A 1 week old male Boer cross breed goat weighing 3 kg was managed intensively in a cemented enclosure. The case was presented to the Ambulatory Unit of the Large Animal Ward, University Veterinary Hospital (UVH), Universiti Putra Malaysia. The kid was fed with colostrum. The patient was presented with swollen knee joint on both forelimbs, series of intermittent seizures, paddling, opisthotonus and torticollis. There was also loss of menace response and pupillary light reflex which indicates loss of sight of both eyes. The kid died and post mortem was conducted with the findings of severe congestion of the brain and spinal cord, mild congestion of the lung, kidney, liver and gastrointestinal tract. There were swelling of the knee joint of both forelimbs and suppurative synovial fluids. Histology revealed there were severe generalised congestion of the lung, brain and spinal cord. There were thickening of the intra-alveolar septa with some inflammatory cells and evidence of spongiosis in the central nervous system.